Canine Leishmaniasis in an Endemic Area for Human Leishmaniasis in Nicaragua - Byron Flores; Brenda Mora-Sánchez; Dayana Torres; Jessica Sheleby-Elías; William Jirón; José Luis Balcazar (Journal of Tropical Medicine)
In this study, the frequency of canines infected with Leishmania spp. in an area endemic to leishmaniasis in humans was determined. A descriptive pilot study was conducted between the months of October and December 2020 on dogs from Rota, a community in the municipality of León, which included 45 specimens from the peridomestic area. Different variables from each specimen were monitored, such as age, sex, breed, body condition, and clinical characteristics, as well as information on the owners and cases of human leishmaniasis presented in less than 5 years. Blood samples were collected from the cephalic vein and peripheral blood was separated. A complete blood count (CBC) was performed using venous blood samples with ethylene diamine tetraacetic acid (EDTA), as well as a conventional PCR was applied for the detection of Leishmania spp. Amastigotes were found in 22% of venous or peripheral blood samples, whereas a high prevalence of 28.89% (95% CI: 14.53–43.24) was found by PCR. Only 1/12 of positive dogs in PCR presented dry exfoliative dermatitis, therefore, there was no significant difference (p≥0.05), the age and sex of the dogs were also not factors associated with infection (p≥0.05). This study reports for the first time the molecular detection of Leishmania in dogs in an endemic area of leishmaniasis in humans in Nicaragua. The high frequency of dogs infected with Leishmania suggests that they play an important role in the transmission cycle of human leishmaniasis.